Palaeoproteomic Profiling of Conservation Layers on a 14th Century Italian Wall Painting. (26th April 2018) - Mackie, Meaghan; Rüther, Patrick; Samodova, Diana; Di Gianvincenzo, Fabiana; Granzotto, Clara; Lyon, David; Peggie, David A.; Howard, Helen; Harrison, Lynne; Jensen, Lars Juhl; Olsen, Jesper V.; Cappellini, Enrico
Abstract: Ahead of display, a non‐original layer was observed on the surface of a fragment of a wall painting by Ambrogio Lorenzetti (active 1319, died 1348/9). FTIR analysis suggested proteinaceous content. Mass spectrometry was used to better characterise this layer and revealed two protein components: sheep and cow glue and chicken and duck egg white. Analysis of post‐translational modifications detected several photo‐oxidation products, which suggest that the egg experienced prolonged exposure to UV light and was likely applied long before the glue layer. Additionally, glycation products detected may indicate naturally occurring glycoprotein degradation or reaction with a carbohydrate material such as starch, identified by ATR‐FTIR in a cross‐section of a sample taken from the painting. Palaeoproteomics is shown to provide detailed characterisation of organic layers associated with mural paintings and therefore aids reconstruction of the conservation history of these objects.